PENGARUH KOMPETENSI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIATING PADA PT. MITRA PRIMA UTAMA - Muhammad, Farakhan; Muhtadin, Imam; Yusuf, Muhammad (Media Riset Bisnis Ekonomi Sains dan Terapan, 2024)
This study aims to find out and analyze the influence of competence and leadership on employee performance with work motivation as a mediating variable in PT. Mitra Prima Utama.The method in this study uses an associative method with a quantitative research approach. Meanwhile, the number of samples used was 52 respondents, using saturated samples for the sampling method. The analysis method used is SEM-PLS.The results of the study are (1) competence has a significant effect on work motivation, (2) leadership has a significant effect on work motivation, (3) competence has a significant effect on employee performance, (4) leadership has a significant effect on employee performance, (5) work motivation has a significant effect on employee performance, (6) competence has a significant effect on employee performance through work motivation, and (7) leadership has a significant effect on performance employees through work motivation.Keywords: Competence, Leadership, Performance, and Work Motivation